2018
DOI: 10.1007/s00484-018-1576-5
|View full text |Cite
|
Sign up to set email alerts
|

Heat loss efficiency and HSPs gene expression of Nellore cows in tropical climate conditions

Abstract: Adaptation is a relevant characteristic to be understood in livestock animals in order to maintain and raise productivity. In Brazil, the Nellore beef cattle are widely disseminated and well-adapted breed that present good thermoregulatory characteristics for tropical environment conditions. Conversely, the physiological and cellular mechanisms required for thermoregulation and thermotolerance in this breed are still limited. The aim of this study was to comprehend the heat loss efficiency at the whole animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
1
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
4
9
1
6
Order By: Relevance
“…However, during the autumn, heifers of the silvopastoral system reached basal levels of cortisol (5–10 ng/mL) 36 , while cows maintained cortisol levels above baseline 37 in both systems. Although a reduction in gene expression of HSP90AA1 in cows allocated in shaded pastures was expected, levels did not differ nor were influenced by variation of climatic conditions, being similar to that found in zebu cattle 38 . It is possible that signaling of thermal stress at the cellular level occurs due to a cumulative exposure, as already reported in some studies 12 , 16 , 39 , and it should be considered that these effects may become evident only after longer periods of animal exposure to the stressor stimulus.…”
Section: Discussionsupporting
confidence: 64%
“…However, during the autumn, heifers of the silvopastoral system reached basal levels of cortisol (5–10 ng/mL) 36 , while cows maintained cortisol levels above baseline 37 in both systems. Although a reduction in gene expression of HSP90AA1 in cows allocated in shaded pastures was expected, levels did not differ nor were influenced by variation of climatic conditions, being similar to that found in zebu cattle 38 . It is possible that signaling of thermal stress at the cellular level occurs due to a cumulative exposure, as already reported in some studies 12 , 16 , 39 , and it should be considered that these effects may become evident only after longer periods of animal exposure to the stressor stimulus.…”
Section: Discussionsupporting
confidence: 64%
“…In the present study, the expression levels of the HSP70 gene were similar between the groups formed and between the breeds studied. Similar HSP70 gene expression results have been reported in Nelore females subjected to heat stress, with no difference between heat-tolerant and non-tolerant animals (Hooper et al, 2019). The expression levels of the HSP70 gene did also not differ between Simmental and Angus animals (Rocha et al, 2019).…”
Section: Discussionsupporting
confidence: 63%
“…Differences in HSPD1 and HSP90AA1 relative expression were observed between Caracu and Nelore breeds, corroborating that zebu cattle are naturally adapted to different climatic conditions. Hooper et al (2018), in a study of Nelore cows, described the expression of HSPD1 fluctuating from 0.93 (42 °C) to 1.20 (40 °C), while we observed that the relative expression of HSPD1 ranged from 0.17 to 7.87 in Nelore and from −1.91 to 6.97 in Caracu steers during sun exposure (36.35 °C to 41.96 °C) in all months studied.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations